2019
DOI: 10.1158/0008-5472.can-18-0238
|View full text |Cite
|
Sign up to set email alerts
|

Bicyclic Peptides as a New Modality for Imaging and Targeting of Proteins Overexpressed by Tumors

Abstract: Molecular imaging of cancers using probes specific for tumor-associated target proteins offers a powerful solution for providing information regarding selection of targeted therapy, patient stratification, and response to therapy. Here we demonstrate the power of bicyclic peptides as targeting probes, exemplified with the tumor-overexpressed matrix metalloproteinase MT1-MMP as a target. A bicyclic peptide with subnanomolar affinity towards MT1-MMP was identified, and its radioconjugate showed selective tumor u… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 49 publications
(45 reference statements)
0
42
0
Order By: Relevance
“…EphA2/CD137-directed tumor immunity BCY12491 exhibited a pharmacokinetic (PK) profile in mice typical of renally eliminated hydrophilic small molecules with a terminal plasma half-life of approximately 2 hr when dosed intraperitoneally (figure 4A). This property of BCY12491, coupled with the small size and rapid tissue penetration of this novel class of molecules, 17 allowed us to test whether efficacy could be achieved with intermittent dosing where plasma drug concentrations fall to very low levels between doses, indeed well below the EC50 in the human PBMC-mouse MC38 cell coculture assays (~0.06 nM, figure 3D). We treated huCD137 transgenic C57Bl/6 mice bearing subcutaneous MC38 tumors with BCY12491 at two doses (5 and 15 mg/kg intraperitoneal) each with two regimens (daily qd or every third day q3d).…”
Section: Target-dependent Tnfr Agonistsmentioning
confidence: 99%
See 1 more Smart Citation
“…EphA2/CD137-directed tumor immunity BCY12491 exhibited a pharmacokinetic (PK) profile in mice typical of renally eliminated hydrophilic small molecules with a terminal plasma half-life of approximately 2 hr when dosed intraperitoneally (figure 4A). This property of BCY12491, coupled with the small size and rapid tissue penetration of this novel class of molecules, 17 allowed us to test whether efficacy could be achieved with intermittent dosing where plasma drug concentrations fall to very low levels between doses, indeed well below the EC50 in the human PBMC-mouse MC38 cell coculture assays (~0.06 nM, figure 3D). We treated huCD137 transgenic C57Bl/6 mice bearing subcutaneous MC38 tumors with BCY12491 at two doses (5 and 15 mg/kg intraperitoneal) each with two regimens (daily qd or every third day q3d).…”
Section: Target-dependent Tnfr Agonistsmentioning
confidence: 99%
“…9 10 Constrained bicyclic peptides or Bicycles are ideally positioned to address these challenges in a way not practically feasible with traditional antibodies 2 3 9 11 or bispecific biological agents. [12][13][14] Bicycles offer small highly modular building blocks, 15 16 rapid tissue distribution and penetration, 17 rapid clearance compared with biologics 16 18 and drug-like characteristics. 18 19 Open access Cas9 gene editing.…”
Section: Introductionmentioning
confidence: 99%
“…[92] Their agents exhibited good tumour penetration, high potency and excellent retention in tumour tissue. [92] These few but compelling examples demonstrate that bicyclic peptides can afford high-contrast theranostic agents. Further research and development is warranted in this sphere.…”
Section: Peptide Analogues Target Clinical Indication/usesmentioning
confidence: 99%
“…In another example, Eder et al identified a bicyclic peptide targeting MT1-MMP (tumoroverexpressed matrix metalloproteinase) with subnanomolar affinity and showed the power of its radioconjugation as a tumor-targeting probe in an HT1080 xenograft mouse model. In vivo studies using different mouse xenograft models showed high affinity to MT1-MMP (Kd at ˜1 nM) and, compared to radiolabeled antibodies directed against the same target, showed rapid tumor penetration characteristics and high potency and chemical versatility [55].…”
Section: Imaging and Diagnosis (Pet Scan Imaging)mentioning
confidence: 99%